AKTIVITAS ANTIMIKROBIA BAKTERI ASAM LAKTAT - Guntur Trimulyono, (Matematika dan Sains, 2011)
The proposes of research were to isolate lactic acid bacteria from vegetable sample and to know their ability to produce antimicrobial compounds. Vegetable samples used were potato, cabbage, sweet potato, and carrot. From those samples it had been isolated 40 isolate predicted as lactic acid bacteria, followed corfirmation test using Gram coloring, catalase test, endospore coloring, and motility. Lactic acid bacteria isolate were screened their ability in inhibiting bacteria tets namely Pediococcus acidilactici LB 42, Staphylococcus aureus ATCC 25923, and Escherichia coli ATCC 35218. The results of reseach showed that four isolates could inhibite growing of Pediococcus acidilactici LB 42, Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218. The antimicrobial subtance produced by BAL isolate was predicted organic acid.